From Contrapuntal Music to Polyphonic Novel: Aldous Huxley’s Point Counter Point - ZENGİN, Mevlüde (Gaziantep University, 2018)
Taken at face value Point Counter Point (1928) written by Aldous Huxley seems to be a novel including many stories of various and sundry people and reflecting their points of view about the world in which they live and about the life they have been leading. However, it is this very quality of the novel that provides grounds for the study of the novel as a polyphonic one. The novel presents to its reader an aggregate of strikingly different characters and thus a broad spectrum of contemporary society. The characters in the novel are all characterized by and individualized with easily recognizable physical, intellectual, emotional, psychological and moral qualities. Each of them is well-contrived through their differences in social status, political views, wealth, etc. Thus, many different viewpoints, conflicting voices, contrasting insights and ideas are heard and seen synchronically in Point Counter Point, which makes it polyphonic. Polyphony is a musical motif referring to different notes and chords played at the same time to create a rhythm. It was first adopted by M. M. Bakhtin to analyze F. M. Dostoyevsky’s fiction. The aim of this study is firstly to elucidate, in Bakhtinian thought, polyphony and then dialogism and heteroglossia closely related to his concept of polyphony; and then to put the polyphonic qualities in Point Counter Point forth, studying the novel’s dialogism and heteroglot qualities